Identification of the 5-HT1A serotonin receptor as a novel therapeutic target in a C. elegans model of Machado-Joseph disease - Joana Pereira-Sousa; Bruna Ferreira-Lomba; Aina Bellver-Sanchis; Daniela Vilasboas-Campos; Jorge H. Fernandes; Marta D. Costa; Mark A. Varney; Adrian Newman-Tancredi; Patrícia Maciel; Andreia Teixeira-Castro (Neurobiology of Disease, 2021)
Machado-Joseph disease (MJD) or Spinocerebellar ataxia type 3 (SCA3) is a progressive neurodegenerative disorder that affects movement coordination leading to a premature death. Despite several efforts, no disease-modifying treatment is yet available for this disease. Previous studies pinpointed the modulation of serotonergic signaling, through pharmacological inhibition of the serotonin transporter SERT, as a promising therapeutic approach for MJD/SCA3. Here, we describe the 5-HT1A receptor as a novel therapeutic target in MJD, using a C. elegans model of ATXN3 proteotoxicity. Chronic and acute administration of befiradol (also known as NLX-112), a highly specific 5-HT1A agonist, rescued motor function and suppressed mutant ATXN3 aggregation. This action required the 5-HT1A receptor orthologue in the nematode, SER-4. Tandospirone, a clinically tested 5-HT1A receptor partial agonist, showed a limited impact on animals' motor dysfunction on acute administration and a broader receptor activation profile upon chronic treatment, its effect depending on 5-HT1A but also on the 5-HT6/SER-5 and 5-HT7/SER-7 receptors. Our results support high potency and specificity of befiradol for activation of 5-HT1A/SER-4 receptors and highlight the contribution of the auto- and hetero-receptor function to the therapeutic outcome in this MJD model. Our study deepens the understanding of serotonergic signaling modulation in the suppression of ATXN3 proteotoxicity and suggests that a potent and selective 5-HT1A receptor agonist such as befiradol could constitute a promising therapeutic agent for MJD.